The Statutes at Large; Being a Collection of All the Laws of Virginia from the First Session of the Legislature, in the Year 1619, Volume 6, Page 531, § 5 - (:unkn) unknown (My University, 1755)
that every person so as aforesaid enlisted (except free mulattoes, negroes, and Indians) shall be armed in the manner following, that is to say: Every soldier shall be furnished with a firelock well fixed, a bayonet fitted to the same, a double cartouch-box.
Keywords: ARMED FORCES